Effect of Germination on Improving Grain Quality, Chemical Composition, Antioxidants, and Phytic Acid in Rice (Oryza sativa) (Atlas Journal of Biology, 2021)
This study aimed to study the effect of the germination process on grain quality, chemical composition for brown rice and comparing them with white rice for use it is on a commercial scale . Three rice varieties namely Sakha 104(Japonica), Giza 178(Japonica- Indica), and Giza 182(Indica) were used in this study. And the three statuses (milled rice, brown rice, and germinated brown rice). A completely randomized design in the factorial arrangement was used in this experiment to determine some cooking and eating quality characters i.e. gelatinization temperature, amylose content and elongation %, Water uptake, hardness, chemical composition: Phytic acid, total antioxidant capacity, and panel test evaluation for rice samples. The results indicated that there were significant differences in amylose content and gelatinization temperature among the three rice statuses and no significant difference in these characters with the three rice varieties under study. Germinated brown rice showed the lowest amylose content (15.58%), followed by brown rice (17.26%) and white rice (18.39%). Brown rice gave the highest temperature followed by germinated brown rice then milled rice. A maximum elongation ratio was observed in Giza178 (Japonica Indica). White rice gave the maximum elongation (47.18%) followed by germinated brown (24.56 %) then brown rice (16.08 %). Japonica rice exhibited lower hardness than indica rice. The strongest value (4.82) was recorded at brown rice, while the weakest value (3.64) was in white rice. The Indica rice variety Giza181 had the highest protein and fat%. The germinated brown rice had the highest value of protein, crude fiber, and fat (7.27, 1.98, and 2.87%, respectively), compared with compared to brown rice and white rice. White rice had lower Phytic acid (%) followed by germinated brown rice, then brown rice. Japonica rice cultivar (Sakha 104) has a higher antioxidant level than Indica rice cultivar (Giza 182)....